2006
DOI: 10.1111/j.1600-0633.2006.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

The status of Arctic charr Salvelinus alpinus in Britain and Ireland

Abstract: –  The Arctic charr occurs in lakes across Britain and Ireland and was previously described here as 15 separate species. Most authorities now agree that all these stocks belong to a single polymorphic species complex Salvelinus alpinus (L.). This fish is given little protection in British and Irish law and there has been a steady loss of natural populations in recent years in all the countries concerned. A few new stocks have been created either intentionally or accidentally. In Scotland, only a small proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 46 publications
(57 reference statements)
0
77
0
Order By: Relevance
“…Within Britain and Ireland, a recent review of the status of Arctic charr by Maitland et al (2007) identified pollution, eutrophication, acidification, afforestation, engineering, exploitation, aquaculture, introduction of alien species and climate change as specific threats to this species. Understanding the impacts in Windermere of eutrophication, climate change and the recent roach expansion, following its introduction c. 100 years ago, thus has a generic importance beyond informing local conservation and fisheries management.…”
Section: Discussionmentioning
confidence: 99%
“…Within Britain and Ireland, a recent review of the status of Arctic charr by Maitland et al (2007) identified pollution, eutrophication, acidification, afforestation, engineering, exploitation, aquaculture, introduction of alien species and climate change as specific threats to this species. Understanding the impacts in Windermere of eutrophication, climate change and the recent roach expansion, following its introduction c. 100 years ago, thus has a generic importance beyond informing local conservation and fisheries management.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent review of the status of this species in Britain and Ireland, Maitland et al (2007) noted that in Scotland at least 12 of 258 such populations are now extinct, as are 4 of 12 native populations in England and 1 of 3 native populations in Wales. Northern Ireland possesses only one native population which is still extant as far as is known.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, the quality of such limited spawning areas is particularly sensitive to the local deposition of fine sediments and as a result the widespread environmental problem of eutrophication has frequently led to declines in recruitment and even to the local extinction of a number of lithophilic species (e.g. Maitland et al, 2007;Winfield et al, 2012;Winfield et al, 2013).…”
Section: Introductionmentioning
confidence: 99%